Preferences of Kazakhstan students in employment field (The Journal of Psychology and Sociology, 2017)
The article devoted to the integration of youth in the socio-economic modern-ization of Kazakhstan’s society. The article deals the problem of young specialists-graduates of universities which they are faced in the period of employment.As a ma-jor determinant of production of living conditions in the area of economic relations risks posed by the growth of youth unemployment, discrimination of professional interests of young people, absence of demand.So from an early age in the period of socialization it is necessary to instilself-confidence, persistence in achieving goals, and most importantly – respect for work.The idea of the Society of Universal La-bouris a practical and pragmatic.Work as a decisive national factor in the condition of global competition to be highlighted.Today the result of the activity should not be just a person with quality basic professional education, but also social and mature personality.This means that new generation is ready to be bearer of social roles that define the socio-economic and political level of the country. Graduates have the challenge of dynamic current level of social production to respond to large-scale changes, to be able to realize their personal and professional potential in terms of social development. The aim of the study is a comprehensive analysis and the identification of trends in the values of modern Kazakhstan youth in the economic context, the local perspective. According to the results of empirical data the authors identify the preferences of Kazakhstan students in employment field.
Keywords: student; graduate; education; sector of employment; labour.